Español - Español; Español; Español, (Ars Pharmaceutica (Internet), 1980)
Lead has been determinated in sorne samples of dirents canned goods of vegetables and also in their containers of tin plateo The ratio Pb food/Pb container conflrms in sorne cases that lead of the containers is transfered to food if the value of the ratio is smaller than one. When the ratio is greater than one, food had lead before to put into a container.